Severance pay in case of moral harassment in Latvia compared with Baltics - Krēmere, Kate (Riga Graduate School of Law, 2022)
The thesis will carry out a review and research on moral harassment and mobbing in Latvia in comparison with the Baltic states. The author researched if the employee is eligible to receive the severance pay in case of mobbing or moral harassment if the termination of the employment relationship is initiated by the employee. The author has reviewed labour relationships in the European Union, Baltic States, the moral harassment and mobbing definitions, and laws governing it. The findings of this thesis are that only in Latvia it is clearly stated that an employee is eligible to receive severance pay in the case he or she is initiating the employment termination because of mobbing or moral harassment.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Private law::Labour law; Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; moral harassment; severance pay; Latvia; Baltic states